CONGRESS VOLUME STELLENBOSCH 2016. (Vetus Testamentum, Supplements, 2017)
This volume presents the main lectures of the 22nd Congress of the International Organization for the Study of the Old Testament (IOSOT) held in Stellenbosch, South Africa, in September 2016. Sixteen internationally distinguished scholars present their current research on the Hebrew Bible, including the literary history of the Hebrew text, its Greek translation and history of interpretation. Some focus on archeological and iconographic sources and the reconstruction of ancient Israelite religion while others discuss the formation of the biblical text and its impact for cultural memory. The volume gives readers a representative view of the most recent developments in the study of the Old Testament.